Community engagement on-site rapid test for chlamydia and gonorrhea among men who have sex with men: a pioneering study in Guangzhou, China - Xiao-Xin Lin; Si-Yan Meng; Wu-Jian Ke; Xiao-Hui Zhang; Liu-Yuan Wang; Yu-Ying Liao; Han Liu; Pei-Zhen Zhao; Chun-Mei Liang; Hui-Ru Chen; Hai-Ying Long; Bin Yang; et al. (BMC, 2022)
Abstract Background Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections are prevalent among men who have sex with men (MSM) in China. However, compared to syphilis and HIV, the testing rate for chlamydia and gonorrhea remains low. The purpose of this pilot study was to evaluate the feasibility for conducting rapid nucleic acid test for chlamydia and gonorrhea in MSM community-based organizations (CBO). Method We recruited our participants through an MSM CBO where free HV and syphilis testing were routinely provided. We collected data including social-demographic background, sexual history, chlamydia and gonorrhea testing history, and reasons for accepting this on-site rapid testing. Urine and/or anorectal swab samples were collected and tested for chlamydia and gonorrhea on-site and the testing results were delivered in about 1.5 h. Positive cases received on-site free treatment. Results From August 2020 to October 2020, 634 MSM visited the CBO for syphilis and HIV testing and 158 (158/634, 24.9%) accepted the on-site chlamydia and gonorrhea rapid test, 135 were finally enrolled. The positive rate fo chlamydia was 16.3% (22/135) and 3.0% (4/135) for gonorrhea, respectively. Only 19.3% participants had previously undergone chlamydia and gonorrhea testing and 68.9% (93/135) participants reported that they had heard of gonorrhea, 47.4% (64/135) had heard of chlamydia. The main reason for testing was "free for charge" (66.2%), followed by "convenient, 'shorter waiting time" (45.2%) and "had high-risk sexual behavior recently" (16.3%). Conclusions This pilot study showed that the chlamydia and gonorrhea infection rate remains high among MSM, while the testing rate was low. On-site rapid testing is feasible and potentially preferred by MSM.